The Study of Rice Potential Production on Irrigation Fields in Deli Serdang Regency - Dewi Novita Sari Saragih; Sumono Sumono; Nazif Ichwan (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Rice in national development order plays an important role as the main food of Indonesian and the main sector as contributor to foreign exchange from non-oil/gas sector. Deli Serdang as one of rice centra region in North Sumatera need to be inspected on wet rice fields condition to hold out and increase rice production. The purpose of this research was to study the rice potential production on irrigation fields in Deli Serdang regency in achieving the maximum level of rice production based on radiation level, time to grow rice, and rice variety. This research also studied the ratio and realibility of existing irrigation networks. In the year of 2009-2013, the result indicated that the irrigation network reability based on productivity, puso and the rice plant index still need to be incrased. The average of ratio between technical irrigation and pra technical and conventional irrigation determined as irrigation degrees of 6,7% and the rice production target was 61%. Key Word: irrigation, potential production, production target, ratio, rice